A Physiological Status Affect Reptiles Thermoregulation’s Strategy: A Review - Oktariansyah, Yadi (BIOVALENTIA: Biological Research Journal, 2025)
As an ectotherm class, reptiles' thermoregulation has unique mechanisms through the combination of physiological traits, behavioral adjustments, and environmental aspects. Reptiles need to do thermoregulation since their body temperature is affected by environmental aspects. Reptiles experience physiological status, which plays an important role in thermoregulatory behavior. This study explores the response of reptiles' thermoregulation strategy under various physiological states, representing facts about the complex thermoregulation mechanism. Specific physiological statuses such as life stage, reproduction status, immune and health system, dehydration, and digestive have been deeply explored by researchers to identify the effects of these traits on reptiles' thermoregulation strategies. These traits significantly affect reptiles' body temperature, such as having low Tb under the dehydration state and choosing higher Tb to promote food digestion under the digestive state. However, the consistency of these results may vary among reptile species that refer more to behavioral adjustment and mating process rather than physiological status. Different life stages and reproduction statuses also influence reptiles' thermoregulation strategy and implicate the evolutionary mechanism for gravid females to obtain a thermally suitable environment, especially for their embryos. Under behavioral adjustments, reptiles alter microhabitat selection to encounter low thermal environments such as water desiccation or climate change threats. Further research that combines physiological traits, behavioral adjustment, and environmental aspects through a biophysical model can contribute to demonstrating how thermoregulation strategies may compromise different physiological statuses. For reptiles, climate change is strongly associated with population loss. Therefore, this study with relevant topics may stand as a proxy for conservation regulation and policymakers to reduce unfavorable thermal environment aspects through habitat degradation.